KAJIAN STRATEGI PEMASARAN ISLAM: STUDI TABUNGAN iB HIJRAH HAJI PADA BANK MUAMALAT KCP. SUMENEP - mujibno mujibno; Mila Octira; Abd. Ghoni (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
Bank Muamalat KCP Sumenep is the first sub-branch office to be pioneered on Madura Island, the sharia marketing strategy has become the basis for its growth, it has been proven that there are many products, both savings, deposits and financing, with a total number of customers reaching 7,000 to date. The iB Hijrah Hajj Savings is one of the idol products for customers who wish to perform Hajj. The researcher describes the Islamic marketing strategy used by Bank Muamalat KCP Sumenep in increasing the number of customers of the iB hijrah haji savings product, and describes the obstacles that occur in marketing the iB hijrah haji savings product. This study uses a qualitative descriptive method. Sources of data obtained from primary data and secondary data with observation techniques, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing, using data triangulation. The results of this study explain that the Islamic marketing strategy in increasing the number of customers of the iB Hijrah Haji Savings Product of Bank Muamalat KCP Sumenep uses a promotion strategy and marketing mix with the performance of Siddiq and Amanah traits taught by Rasulullah. Optimization of segmenting, targeting and positioning becomes a driving force in every product. The obstacles faced were the high level of competition, the co-19 pandemic, and the lack of technological knowledge from customers. Therefore, the existence of an Islamic marketing strategy spurred a sense of enthusiasm on the part of the Muamalat KCP bank. Sumenp to continue to provide the latest innovations so that the products they have remain the choice of customers.